2021
DOI: 10.3389/fphar.2021.612659
|View full text |Cite
|
Sign up to set email alerts
|

Novel Methods and Approaches for Safety Evaluation of Nanoparticle Formulations: A Focus Towards In Vitro Models and Adverse Outcome Pathways

Abstract: Nanotoxicology is an emerging field employed in the assessment of unintentional hazardous effects produced by nanoparticles (NPs) impacting human health and the environment. The nanotoxicity affects the range between induction of cellular stress and cytotoxicity. The reasons so far reported for these toxicological effects are due to their variable sizes with high surface areas, shape, charge, and physicochemical properties, which upon interaction with the biological components may influence their functioning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 232 publications
(300 reference statements)
0
43
0
Order By: Relevance
“…However, based on the results already published, it has been reported that NMs can cause reactive oxygen species (ROS) production either directly or indirectly during toxicity or cytotoxicity, leading to oxidative stress (Figure 1). This could be due to the existence of pro-oxidant functional groups on their reactive surfaces or NM-cell interactions [2,[11][12][13]. Oxidative stress can cause damage of DNA (which includes induction of gene mutations, DNA strand breakages, and chromosomal fragmentation) and subsequently apoptosis.…”
Section: Possible Mechanism Of Nanomaterials Toxicitymentioning
confidence: 99%
See 4 more Smart Citations
“…However, based on the results already published, it has been reported that NMs can cause reactive oxygen species (ROS) production either directly or indirectly during toxicity or cytotoxicity, leading to oxidative stress (Figure 1). This could be due to the existence of pro-oxidant functional groups on their reactive surfaces or NM-cell interactions [2,[11][12][13]. Oxidative stress can cause damage of DNA (which includes induction of gene mutations, DNA strand breakages, and chromosomal fragmentation) and subsequently apoptosis.…”
Section: Possible Mechanism Of Nanomaterials Toxicitymentioning
confidence: 99%
“…Oxidative stress can cause damage of DNA (which includes induction of gene mutations, DNA strand breakages, and chromosomal fragmentation) and subsequently apoptosis. NMs (or nanoparticles) have also been reported to induce inflammation, resulting in toxicity and promoting cell death by inducing toxic by-products like complement proteins and ROS or receptorinduced necrosis/apoptosis (Figure 1) [2,10,[12][13][14]. Furthermore, oxidative stress may provoke the release of pro-inflammatory mediators through phosphoinositide 3-kinase (PI3-K) pathways, mitogen-activated protein kinase (MAPK), and nuclear factor-κB (NF-κB), indicating a mutual correlation between oxidative stress and inflammation.…”
Section: Possible Mechanism Of Nanomaterials Toxicitymentioning
confidence: 99%
See 3 more Smart Citations